Eco-friendly yield-scaled global warming potential assists to determine the right rate of nitrogen in rice system: A systematic literature review. (15th February 2021) - Islam Bhuiyan, Mohammad Saiful; Rahman, Azizur; Kim, Gil Won; Das, Suvendu; Kim, Pil Joo
Abstract: Rice paddies are one of the largest greenhouse gases (GHGs) facilitators that are predominantly regulated by nitrogen (N) fertilization. Optimization of N uses based on the yield has been tried a long since, however, the improvement of the state-of-the-art technologies and the stiffness of global warming need to readjust N rate. Albeit, few individual studies started to, herein attempted as a systematic review to generalize the optimal N rate that minimizes global warming potential (GWP) concurrently provides sufficient yield in the rice system. To satisfy mounted food demand with inadequate land & less environmental impact, GHGs emissions are increasingly evaluated as yield-scaled basis. This systematic review (20 published studies consisting of 21 study sites and 190 observations) aimed to test the hypothesis that the lowest yield-scaled GWP would provide the minimum GWP of CH4 and N2 O emissions from rice system at near optimal yields. Results revealed that there was a strong polynomial quadratic relationship between CH4 emissions and N rate and strong positive correlation between N2 O emissions and N rate. Compared to control the low N dose emitted less (23%) CH4 whereas high N dose emitted higher (63%) CH4 emission. The highest N2 O emission observed at moderated N level. In total GWP, about 96% and 4%, GHG was emitted as CH4 and N2 O, respectively. The mean GWP of CH4 and N2 O emissions from rice was 5758 kg CO2 eq ha −1 . The least yield-scaled GWP (0.7565 (kg CO2 eq. ha −1 )) was recorded at 190 kg N ha −1 that provided the near utmost yield. This dose could be a suitable dose in midseason drainage managed rice systems especially in tropical and subtropical climatic conditions. This yield-scaled GWP supports the concept of win–win for food security and environmental aspects through balancing between viable rice productivity and maintaining convincing greenhouse gases. Graphical abstract: Image 1 Highlights: Compared to control at low N dose emitted less (23%) CH4 while at high N dose emitted higher (63%) CH4 emission. Compared to control, N2 O emission was 10 % less at low N rate whereas 289 % higher at moderate N rate. In total GWP, about 96% and 4%, GHG were emitted as CH4 and N2 O, respectively. The least yield-scaled GWP (0.7565 (kgCO2 eq. ha −1 )) was recorded at 190 kg N ha −1 . Abstract : Main findings: A strong polynomial quadratic relationship between CH4 emissions and N rate and a strong positive correlation between N2 O emissions and N rate were observed. Compared to control at low N dose emitted less (23%) CH4 while at high N dose emitted higher (63%) CH4 emission. The least yield-scaled GWP (0.7565 (kgCO2 eq. ha −1 )) was recorded at 190 kg N ha −1 that provided the near utmost yield.